Effects of Steam Pretreatment and Delignification Time on Balsa Wood Polyvinyl Alcohol Composites - Sena Maulana; Fajar Aditya Julyatmojo; David Raja Endar Ambarita; Laras Widi Setia Ningrum; Jabosar Hamonangan Panjaitan; Muhammad Iqbal Maulana; Sarah Augustina; Muhammad Aizat Abdul Ghani (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
The effect of controlled steam pretreatment on polyvinyl alcohol/balsa wood composites was investigated. Controlled steam was applied prior to subsequent sodium chlorite-acetic acid delignification of balsa wood and its impregnation with polyvinyl acetate (PVA). Low-density balsa veneers were either not subjected to steam or were steamed at 126 °C for 1 h. Wood delignification was carried out in a 1% solution of sodium chlorite-acetic acid at 80 °C for 45, 90, or 180 min. The samples were further bleached in a 3% hydrogen peroxide solution and vacuum-impregnated with 5% PVA. The Wood-PVA system was monitored using color, tensile, FTIR, and X-ray diffraction analyses. The steam-pretreated and delignified for 90 min sample (90S) exhibited the best characteristics, showing a tensile strength of 3.39 MPa and Young’s modulus of 112.36 MPa. The obtained data indicated continuous removal of lignin and hemicellulose, much stronger PVA-cellulose interactions, and preservation of cellulose in its native cellulose I state without a significant decrease in crystallinity. The proposed treatment represents a reproducible way to convert balsa wood into a stiff, formaldehyde-free, and low-density composite material available for implementation in modern building technologies.